Інноваційне наповнення організації виробничої діяльності промислових підприємств - Петрович, Й. М.; Савоніна, Н. С.; Petrovych, Yo.; Savonina, N. (Видавництво Львівської політехніки, 2018)
Висвітлено можливості інноваційного наповнення організування виробничої діяльності промислових підприємств, серед яких: дбайливе виробництво, теорія обмежень та інші заходи. Показано сферу та межі застосування показника загальної ефективності обладнання. Розглянуто взаємозв’язок між показником загальної ефективності обладнання та енергоефективністю виробництва. Охарактеризовано види втрат у виробничому процесі, показано, як ці втрати впливають на рівень та ефективність споживання енергії. Доведено, що адекватне управління устаткуванням дає змогу знизити енергетичні витрати та сприяє впровадженню врівноважених управлінських рішень

The synthesis and coverage of foreign experience in the organization of production at industrial enterprises has a diverse focus and encompasses methods that increase the productivity of their productive activities in various ways. In this context, the Japanese experience of organizing production deserves special attention. The advantages of its application are demonstrated by Japanese companies that are world leaders in terms of achieved product quality, productivity, stock optimization, in-house and other costs. In the article are considered such methods in the organization of production as lean production, the theory of constraints, and others used for the production of goods and services using various resources and aimed at ensuring defect-free production at a speed that meets the needs of consumers by eliminating unnecessary losses. The overall efficiency of equipment (OEE) as a system for analyzing the overall efficiency of the equipment is considered. It is designed to control and increase the efficiency of production and is based on the measurement and processing of specific production indicators. Types of losses that affect the efficiency of the equipment are described. The relationship between OEE and energy efficiency of production is investigated. The high level of defective products that do not meet the quality standards, inefficient production planning, the slow operation of equipment is all a vivid example of the causes of energy losses. The use of the considered methodologies will allow identifying limiting factors – “bottlenecks” of production activities and determining the degree of achievement of goals as a result of the introduction of modern progressive methods of organizing production activities in the enterprise
Innovative content for organizing production activities of industrial enterprises
Keywords: інновації; організування; виробництво; гнучкість; адаптація; обладнання; ефективність; результативність; innovation; organization; production; flexibility; adaptability; equipment; efficiency; performance; 338.3; 330.3